Adhesion and Growth of Vascular Smooth Muscle Cells on Nanostructured and Biofunctionalized Polyethylene - Novotna, Katarina; Bacakova, Marketa; Kasalkova, Nikola Slepickova; Slepicka, Petr; Lisa, Vera; Svorcik, Vaclav; Bacakova, Lucie (Materials (Basel, Switzerland), 2013)
Cell colonization of synthetic polymers can be regulated by physical and chemical modifications of the polymer surface. High-density and low-density polyethylene (HDPE and LDPE) were therefore activated with Ar⁺ plasma and grafted with fibronectin (Fn) or bovine serum albumin (BSA). The water drop contact angle usually decreased on the plasma-treated samples, due to the formation of oxidized groups, and this decrease was inversely related to the plasma exposure time (50-300 s). The presence of nitrogen and sulfur on the polymer surface, revealed by X-ray photoelectron spectroscopy (XPS), and also by immunofluorescence staining, showed that Fn and BSA were bound to this surface, particularly to HDPE. Plasma modification and grafting with Fn and BSA increased the nanoscale surface roughness of the polymer. This was mainly manifested on HDPE. Plasma treatment and grafting with Fn or BSA improved the adhesion and growth of vascular smooth muscle cells in a serum-supplemented medium. The final cell population densities on day 6 after seeding were on an average higher on LDPE than on HDPE. In a serum-free medium, BSA grafted to the polymer surface hampered cell adhesion. Thus, the cell behavior on polyethylene can be modulated by its type, intensity of plasma modification, grafting with biomolecules, and composition of the culture medium.
Keywords: albumin; fibronectin; wettability; cell spreading area; tissue engineering; biocompatibility; bioactivity; nanoscale surface roughness; plasma treatment